Land use impacts on climate - Negi, Manoj; Monga, Jyoti (SCITUS Academics LLC, 2016)
Since the industrial revolution, climate changes caused by greenhouse gas emissions have attracted the attention globally from a diverse community including both politicians and scientists; however, the pending issues on the research of the climatic impact of land cover and land-use changes via terrestrial bio geophysical processes is far from resolved. The scientific community needs to provide comprehensive scientific support for global change adaptation. Land cover and land use changes directly lead to change in the surface condition, thereby changing the surface albedo and surface roughness, and then affects surface heat balance and water cycles. In addition, the urban expansion causes aggravation of urban heat island effect. It is of significance to understand climatic impacts accompanied by bio geophysical processes induced by land-use changes, which is critical for food safety, extreme climate, biodiversity protection, and a series of problems. Land use change, in turn, is occurring in the context of climate changes at a variety of scales.